Health Literacy and Self-Rated Health among Homeless Adults - Odoh, Chisom (Health Behav Res, 2019)
Poor health literacy reduces the efficacy of behavior change interventions, hampers management of health conditions, and attenuates understanding of the prevention and treatment of diseases. Poor health literacy has also been linked to fair/poor self-rated health in domiciled samples; however, there is a paucity of studies on the relation amongst homeless adults, who bear a disproportionate burden of disease and disability and require high level of care and access to health services. Here, we examined the association between health literacy and self-rated health among a convenience sample of homeless adults. Participants were recruited from six homeless-serving agencies in Oklahoma City (N = 575; 63% men, M(age) = 43.6±12.3). Logistic regression was used to assess the association between health literacy (confidence completing medical forms: extremely/quite a bit vs somewhat/little bit/not at all) and self-rated health (poor/fair vs good/very good/excellent) controlling for age, subjective social status, education, race, sex, income, health insurance, employment, social security recipient status, diabetes diagnosis, high blood pressure diagnosis, and high cholesterol diagnosis. In the adjusted model, health literate homeless individuals had greater odds of endorsing good/very good/excellent self-rated health compared to those somewhat/a little bit/not at all confident completing medical forms (AOR = 2.02, [CI(95%) = 1.35-3.02]). Interventions targeted at adjusting reading level and comprehensibility of health information are needed for homeless individuals with poor/limited health literacy, which may ultimately impact their self-rated health. Shelters and homeless-serving agencies could host classes focused on practical skills for enhancing health literacy and/or provide navigation services.